2018
DOI: 10.3390/su10124387
|View full text |Cite
|
Sign up to set email alerts
|

Model of Predicting Cost Overrun in Construction Projects

Abstract: During the construction phase, significant differences between the planned and actual costs of construction projects frequently occur. The paper describes the concept of a model of prediction of the increase in the costs of construction works in relation to those planned. The assumption of the model is to determine the probability of the cost increase for the elements of the object for which it is the largest. A fuzzy Mamdani inference method was proposed for the selection of the elements to be evaluated. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 21 publications
0
33
0
1
Order By: Relevance
“…Project Management System (C 3-4 ) measures how the contractor plans and organizes their resources for installing the solar panel [75,82]. Progress Cost Control (C 3-5 ) evaluates relative cost of the process towards the completion of the installation of the solar panels, including checks and restrictions made to reasonably minimize cost [83,84].…”
Section: Technical Capability (C 2 )mentioning
confidence: 99%
“…Project Management System (C 3-4 ) measures how the contractor plans and organizes their resources for installing the solar panel [75,82]. Progress Cost Control (C 3-5 ) evaluates relative cost of the process towards the completion of the installation of the solar panels, including checks and restrictions made to reasonably minimize cost [83,84].…”
Section: Technical Capability (C 2 )mentioning
confidence: 99%
“…This predisposition for considerable time and cost deviations during the execution of construction work, was one of the main causes of the real estate bubble burst. The problem related to cost overruns and deviations in building delivery times also extends to the international context, where some authors identify an average cost overrun of 12.22% in construction and engineering projects [1,2]. Some authors state that only less than 25% of the projects awarded in public bids remain within 10% of their contractual deadlines [3].…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, various mathematical methods and tools have been used to solve the problem of predicting construction costs and cost overruns in construction projects, such as simple and multiple linear regression, "soft computing" methods, such as: neural networks, machine learning, fuzzy logic, etc. (Plebankiewicz, 2018). It was found that the experience of contractors in previous construction projects is an important element that can help to avoid mistakes and increase the chances of success of future projects in the construction phase.…”
Section: Introductionmentioning
confidence: 99%